Teaching for a Broken World - Gayatri Chakravorty Spivak (Anglica. An International Journal of English Studies)
This essay offers methodological suggestions for using the humanities to create a general will for social justice. The enthusiasm of the initial years will naturally cool. We must continue to try to keep to the initial principles, even as we satisfy institutional norms. In restoring the ethical base of society through humanities teaching – teaching the other-directed practice of learning rather than keeping track of the production of knowledge – we remind the corporate university that the restoration of juridico-ethics to society cannot be sacrificed in the name of revenue-production. The model of a new International where the classroom is the locus of the production of individuated collectivities is proposed. The imperatives of planetarity are touched on. Activist reading is seen as a relay race. We are reminded that every self-declared rupture is also an unacknowledged repetition. All this to be undertaken globally by using the already-existing model of the international civil society.